2012
DOI: 10.1111/j.1468-0009.2012.00682.x
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Cost‐Effectiveness Analysis for Pediatric Immunization in Developing Countries

Abstract: Greater attention to pediatric interventions and donor funding in the conduct of CEA could lead to better policies and thus more worthwhile and good-value programs to benefit children's health in developing countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 87 publications
(87 reference statements)
0
5
0
Order By: Relevance
“…For example Gauvreau et al [22] argued that most studies of paediatric immunization programs should extend their time horizons for evaluating the impacts of donor funding because implementation costs of such programs tend to be incurred predominantly at the beginning of intervention scale-up. As further examples, Menzies et al [23] and Gupta et al [24] showed that unit costs of ART delivery fall by 50% or more in the Figure 2. One-way sensitivity analysis of I4TB (Direct effect).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…For example Gauvreau et al [22] argued that most studies of paediatric immunization programs should extend their time horizons for evaluating the impacts of donor funding because implementation costs of such programs tend to be incurred predominantly at the beginning of intervention scale-up. As further examples, Menzies et al [23] and Gupta et al [24] showed that unit costs of ART delivery fall by 50% or more in the Figure 2. One-way sensitivity analysis of I4TB (Direct effect).…”
Section: Discussionmentioning
confidence: 96%
“…As further examples, Menzies et al . [23] and Gupta et al . [24] showed that unit costs of ART delivery fall by 50% or more in the years following initial scale‐up, and Suwanthawornkul et al .…”
Section: Discussionmentioning
confidence: 99%
“…Economic evaluation has become increasingly important in guiding health policy on the reimbursement of new interventions, including vaccines. 1 Over the past decades, the number of new pediatric vaccines has increased. 2 The preferred approach to evaluate new vaccines is through integrating effects on mortality and health-related quality of life (HRQoL) to provide evidence on value for money [3][4][5] and to inform priority setting in the health sector.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] This pattern was also identified in vaccination-specific reviews. 1,14 Interestingly, cost-per-DALY studies are also common in Australia and New Zealand, with the Assessing Cost-Effectiveness-Prevention studies in Australia, 15 and the BODE (Burden of Disease Epidemiology, Equity, and Cost-Effectiveness Programme) 3 in New Zealand, which used the terminology of health-adjusted life-years or QALYs gained, but used disability weights rather than utility weights. 16 The interchangeability between both measures has been questioned in literature, and some evidence indicates the health benefits gained using DALYs are lower than when QALYs are used, 3,7,17 whereas other studies have shown the differences between QALY-and DALY-based ratios is modest and may not affect cost-effectiveness conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…Very few analyses, however, have ventured into the realm of full cost‐benefit analysis, since health care analysts and providers hesitate to place a specific dollar value on potential health outcomes. But cost‐effectiveness analysis, a near relative of cost‐benefit analysis, has been commonly used and often is preferred because it expresses health benefits in natural units, such as quality‐adjusted life years (QALYs) gained or disability‐adjusted life years (DALYs) prevented …”
mentioning
confidence: 99%